The Effectiveness of the Drill Method in Teaching Pianika to Children with Cerebral Palsy at SLB Rumah Pintar Salatiga - Algifari Khosyi Zildjian; Eko Raharjo (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to evaluate the effectiveness of pianica music learning using the drill method in improving fine motor skills among children with cerebral palsy (CP) at the Rumah Pintar Special Needs School in Salatiga. The research employed a qualitative case study approach involving five students with varying degrees of CP severity. Data were collected through in-depth interviews, observation, and documentation to assess the impact of repetitive and structured practice using the pianica as a learning medium. The findings revealed significant improvements in fine motor skills, particularly in hand-eye coordination, finger strength, and rhythm pattern comprehension. Initially, students struggled with simple rhythmic patterns, but after 12 sessions, their success rate increased to 80% with more complex rhythms. The drill method also had a positive impact on students’ motivation and confidence. Previously passive students became more enthusiastic and willing to take on new challenges. The study also found that the degree of CP severity affected the learning outcomes, highlighting the need for individualized teaching approaches. In conclusion, the drill method using the pianica is effective in enhancing fine motor abilities and supporting the psychological development of children with CP. This approach can serve as a relevant strategy for special education and is worth adopting more broadly.